STRATEGI PENCERITAAN FILM-FILM BERPRESTASI KARYA MAHASISWA FILM UMN YANG DIPRODUKSI DI TENGAH PANDEMI COVID-19 - Perdana Kartawiyudha (Texture:Art and Culture Journal, 2022)
The COVID-19 pandemic has forced filmmakers to set special production strategies so that their production can run safely. For this reason, the first thing that can be done is to design the right story for the COVID-19 pandemic situation at the development stage. This study tries to explore the storytelling strategies taken by screenwriters in telling their stories in the context of the COVID-19 pandemic. The films selected for this analysis were films from Moving Image Production (MIP) students at the UMN Film Study Program which were produced with awareness of the COVID-19 pandemic and managed to participate in both national and international curated exhibition and gain some acknowledgment. The method of this research is qualitative and was done by conducting content analysis on existing narrative documents (synopsis, characterization, and scenarios) as well as literature review on related topics, themes and theories related to storytelling, specifically focusing on the analysis of characters and story settings.